T1 Mapping for DCE-MRI / Nurun Najwa Kamaluzaman - Nurun Najwa , Kamaluzaman (2013)

(untitled)
The main purpose of this study is to develop a T1 mapping technique by using variable flip angle (VFA) technique based on fast spoiled gradient echo (FSPGR) pulse sequence and to implement the technique in in vivo imaging. FSPGR imaging was performed on a set of T1 gel phantoms with different concentrations of Gd3Cl by using 1.5 Tesla MRI. To determine the T1 values of the gel phantoms, signal intensities from three sets of images produced by using three different flip angles were fitted pixel-by-pixel by using spoiled gradient echo equation. The T1 values calculated were displayed as a T1 map. The T1 values of the gel phantoms estimated with selected ROI were compared with the values determined by a standard T1 measurement technique i.e. inversion recovery [TR = 6500 ms, TE = 7.51 ms, inversion time (TI) = 50, 300, 550, 800, 1050 ms]. The VFA mapping was then performed on four healthy volunteers to assess its effectiveness in clinical imaging. The mapping was performed on the right thigh of the volunteer for two different anatomical orientations, axial and coronal. The T1 values of the fat and muscle estimated with selected ROI were compared with different orientations, scanning dimensions and pulse sequences. The comparison of T1 value for different orientation was performed for three pulse sequences i.e., Multislice Two Dimensional (M2D) FSPGR, three iv dimensional (3D) FSPGR and Liver acceleration volume acquisition (3D LAVA) at axial and coronal orientations. The comparison of T1 value for scanning technique was performed using M2D FSPGR and 3D FSPGR pulse sequences. The comparison of T1 value for different pulse sequence was performed using 3D FSPGR and 3D LAVA pulse sequences. The curve fitting and image analysis were performed by using Matlab software.The T1 values of the gel phantoms produced by using VFA technique of 3D FSPGR and 3D LAVA were close to the values determined by the IR method. The T1 values estimated by 2D FSPGR showed different values respect to IR method. The T1 values produced on volunteer at axial orientation was higher than values at coronal orientation. The T1 values estimated using 3D FSPGR and 2D FSPGR showed in large difference. The T1 values estimated using 3D FSPGR and 3D LAVA pulse sequence showed a smaller difference. We have developed a technique to map the T1 values by using VFA spoiled gradient echo technique. The technique has been successfully implemented on T1 gel phantoms and healthy volunteers. Further works will include more volunteers for improve the validity of this study.